Fear of progression after cancer recurrence: a mixed methods study - Stewart, Ross James; Humphris, Gerald Michael; Donaldson, Jayne; Cruickshank, Susanne (Frontiers in Psychology, 2024)
Background The recurrence of cancer will significantly impact an individual’s quality of life (QoL) as they adjust to living with a condition that is often incurable. Patients remain at risk of further progression following recurrence, but fear of cancer progression (FOP) at this time is not commonly examined. Importantly, these fears are known to reach levels in which there are consequences for QoL. Methods This study sought to explore levels of FOP, health-related QoL, anxiety, and depression in patients after a recurrence of their cancer in a longitudinal manner. With the study taking place throughout the COVID-19 pandemic, an assessment of fears related to cancer and the pandemic was included. A sequential mixed method approach was employed for complementarity and expansion purposes. A questionnaire was administered to 44 participants on three different occasions one month apart. A sub-sample of 10 participants then took part in semi-structured interviews. Findings FOP was present at moderate levels in patients with a cancer recurrence, with over a third of the sample reaching levels considered dysfunctional. Levels of fear were stable over three months and were not predicted by select demographic or clinical factors. On average, depression was low, but anxiety reached mild levels. Challenges to health-related QoL were evident. Low levels of concern about COVID-19 in relation to cancer were reported. Integrated findings provided more nuanced answers to the research questions, including more specific worries about cancer progression. Implications Findings support the development of psychosocial interventions to manage FOP, and future recommendations are provided. Identifying the presence of fears not commonly screened for after cancer recurrence adds to the existing knowledge in this area. Through acknowledging and attending to the psychosocial impact of FOP, healthcare professionals can provide tailored support to enhance the well-being of those with a recurrence of their cancer.